2018
DOI: 10.1007/s11116-018-9922-3
|View full text |Cite
|
Sign up to set email alerts
|

Has heavy vehicle tolling in Europe been effective in reducing road freight transport and promoting modal shift?

Abstract: During the last few decades, the European Union has promoted distance-based charges on heavy goods vehicles for the use of main roads as a means of funding the infrastructure and internalizing external costs. This approach has progressively been implemented by many European nations. From a macro perspective, this paper explores the impact of heavy vehicle tolling on road freight demand in the countries where it has been implemented. To that end, we develop a dynamic panel data methodology to analyze the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The experience of countries has shown that international emission trading was a cost effective way to reduce global Transport CO₂ emission. Emissions charges were an effective way for the Government to intervene in order to environmental protection (Burchell, Ison, Enoch, & Budd, 2019;Camporeale, Caggiani, Fonzone, & Ottomanelli, 2019;Carbone, Helm, & Rutherford, 2009;Fujimori et al, 2016;Fujimori, Masui, & Matsuoka, 2015;Gomez & Vassallo, 2020;H. Wang, Shi, Xue, He, & Liu, 2022;X.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The experience of countries has shown that international emission trading was a cost effective way to reduce global Transport CO₂ emission. Emissions charges were an effective way for the Government to intervene in order to environmental protection (Burchell, Ison, Enoch, & Budd, 2019;Camporeale, Caggiani, Fonzone, & Ottomanelli, 2019;Carbone, Helm, & Rutherford, 2009;Fujimori et al, 2016;Fujimori, Masui, & Matsuoka, 2015;Gomez & Vassallo, 2020;H. Wang, Shi, Xue, He, & Liu, 2022;X.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Union has indeed since long promoted the implementation of a unique distance-based toll system, and approved in 1999 a new road charging directive. The main idea was to charge trucks according to different parameters under the principle of ‘user-pays’ (Gomez and Vassallo 2020; Shepherd 2008). It firstly led to the implementation of the Euro-Vignettes, a fare under the shape of a tax stickers that vehicles over 3.5 tonnes must pay to travel on the road network in European countries.…”
Section: Introductionmentioning
confidence: 99%
“…Without them, most of the goods cannot be delivered, and the offer cannot reach the demand. To handle a big change, these companies often recreate themselves, adapt and start operate differently (Gomez and Vassallo 2020). However, it is important to note that Broaddus and Gertz (2008) show that distance tolls have not strongly impacted the sector.…”
Section: Introductionmentioning
confidence: 99%